COMMUNITY ECONOMIC EMPOWERMENT THROUGH THE DEVELOPMENT OF MICRO AND SMALL AND MEDIUM ENTERPRISES: A CASE STUDY IN ALAMENDAH TOURISM VILLAGE - Willya Achmad; Nunung Nurwati; Rd. Siti Sofro Sidiq (JEES: Journal of Economic Empowerment Strategy, 2023)
This research on Community Economic Empowerment in Alamendah Tourism Village is to find out if there are tourist villages that are able to maintain economic balance. This Alamendah Tourism Village makes more use of its natural potential, but economic resources through the MSME sector are also important in this economic empowerment. The development of micro, small, and medium-sized enterprises (MSMEs) is anticipated to be able to maintain the economic equilibrium of a community as a result of the construction of a tourism village. This study seeks to determine the outcomes of community economic empowerment in Alamendah Tourism Village through the development of MSMEs. This study employs a qualitative methodology with descriptive methods. The results of the study show that the community's economic empowerment in the Alamendah tourism village through MSMEs can be increased by encouraging local entrepreneurship, providing easy access to financing, improving product quality, strengthening marketing and promotion, and actively involving the community. With the synergy of local business actors, village government, NGOs and related parties, tourism villages can achieve sustainable economic growth, improve people's welfare, and create an inclusive and competitive local economy.